Electricity " Its functiona ,and role in the rural development process Anthropological stydy in the coastal village (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study states that the rural community at the Syrian coast witnessed actually group of changes that were in touch with many sides of its structure and different functions, thus takeoff of the first light sparks was as an indication of the rural community entering into the first stages of the modernization and comprehensive development epoch. The study got to a conclusion stating that: entering electricity into the coastal countryside resulted truly in extension of utilization area in the agricultural field and public service, and then electricity provided the objective pivots to attain the countryside stability, and pushed the development wheel of its possibilities forward just as the urbanized community, because the sustainable development is completely and continuously societal operation. In spite of the important changing role that electricity played in the rural developmental operation, but the ambition is still larger in extending the utilization of this type of energy densely in both agricultural industry and tourist industry sectors, where all basic factors of promoting these two sectors in the coastal countryside are available, what ensure a rich source for supporting the national economy that consequently sustains the national returns of the foreign currency and forms a prop in the operation of attaining requirements of social welfare of the entire society.